Expression, Prognostic Value, and Functional Mechanism of the KDM5 Family in Pancreatic Cancer - Duan, Yunjie; Du, Yongxing; Gu, Zongting; Zheng, Xiaohao; Wang, Chengfeng (Frontiers in Cell and Developmental Biology, 2022)
Background: The histone lysine demethylase KDM5 family is an important epigenetic state-modifying enzyme family. Increasing evidence supports that epigenetic abnormalities in the KDM5 family are related to multiple cancers in humans. However, the role of the KDM5 family in pancreatic cancer is not clear, and related research is very scarce. Methods: R software, Kaplan–Meier Plotter, cBioPortal, TIMER, LinkedOmics, STRING, Metascape, TISIDB and the GSCA Lite online tool were utilized for bioinformatics analysis. Results: KDM5A/B/C was significantly overexpressed in many kinds of tumor tissues, including pancreatic adenocarcinoma (PAAD), while the expression of KDM5D was significantly downregulated. The high expression of KDM5A/B/C was related to poor clinical features, such as worse treatment efficacy, higher tumor grade, and more advanced clinical stage. Patients with a family history of breast cancer and melanoma, history of drinking or history chronic pancreatitis were more likely to have KDM5A/B/C gene abnormalities, which were related to a variety of adverse clinical features. The results of gene ontology (GO) and kyoto encyclopedia of genes and genomes (KEGG) pathway analyses of the KDM5 family and its 800 co-expressed genes showed that many gene terms related to cell proliferation, migration and many carcinogenic pathways. Notably, we found that the expression level of KDM5A/B/C was positively correlated with the expression of multiple key driver genes such as KRAS, BRCA1, BRCA2 etc. In addition, PPI network analysis showed KDM5 family proteins have strong interactions with histone deacetylase family 1 (HDAC1), which could modify the lysines of histone H3, and co-act on many pathways, including the "longevity-regulating pathway" and "Notch signaling pathway". Moreover, the upregulation of KDM5A/B/C expression was associated with an increase in the infiltration of B cells, CD8+ T cells and other infiltrating immune lymphocytes and the expression levels of immune molecules such as NT5E and CD274.Interestingly, the overexpression of KDM5A/C was also corelated with reduced sensitivity of pancreatic cancer cells to many kinds of pancreatic cancer-targeting or chemotherapeutic drugs, including gemcitabine and paclitaxel. Conclusion: KDM5 family members may be prognostic markers and new therapeutic targets for patients with pancreatic cancer.